Eating healthy and sustainable: consumer awareness, perceptions and attitude towards mushroom consumption in Kigali, Rwanda - Ndayisaba, Felix; Hatungimana, Mediatrice; Umarishavu, Françoise; Teuber, Ramona (Frontiers in Sustainable Food Systems, 2025)
While the health and sustainability aspects of diets in high-income countries have received great attention, the dearth of research on food-related health and sustainability aspects in low-income countries needs to be addressed. Focusing on mushroom consumption as an example of a healthy and sustainable dietary practice, this study examines consumers’ awareness and knowledge towards healthy and sustainable eating and explores the attitudes and barriers towards mushroom consumption in Kigali, Rwanda. Data from 16 in-depth interviews and two focus group discussions were thematically analyzed using MaxQDA 24.3.0 through the lens of the Theory of Planned Behavior and the New Ecological Paradigm Scale. The results indicate that awareness on food related sustainability issues is limited, and most respondents reported being indifferent to environmental concerns in their food decision making process. While healthy diets are perceived as those containing plenty of vegetables and fruits, unhealthy diets are described as those containing high amounts of sugar, salt and fats, including overconsumption of meat products. The results also highlight mixed attitudes toward mushroom consumption, shaped by cultural misconceptions, limited availability, and gaps in cooking knowledge. The findings underscore the need for interventions to enhance awareness on healthy diets and sustainability, while mushroom consumption could be supported by developing the value chain to ensure all-season availability, accessibility and affordability.